2016
DOI: 10.1097/inf.0000000000001050
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia Caused by Raoultella ornithinolytica in Two Children

Abstract: We encountered 2 immunocompromised children complicated by Raoultella ornithinolytica bacteremia. One had received methylprednisolone pulse therapy for IgA nephropathy, and the other had leukopenia because of chemotherapy for leukemia. Both children had no specific symptoms, and R. ornithinolytica bacteremia was identified by routine blood culture. Both patients were successfully treated with antibiotic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 11 publications
0
24
1
1
Order By: Relevance
“…8 In the second case, the isolated strain was susceptible to meropenem, minocycline and amoxicillin/ clavulanic and resistant to levofloxacin, piperacillin and TMP-SMX. 8 Treatment consisted of ceftriaxone (2 weeks) and meropenem (17 days) respectively with clinical improvement in both cases. 8 Abbas et al (2018) reported a case of neonatal sepsis with a multidrug resistant strain of R. ornithinolytica isolated in blood cultures of a 12 hrs-old infant.…”
Section: Bloodstream and Other Infectionsmentioning
confidence: 95%
See 3 more Smart Citations
“…8 In the second case, the isolated strain was susceptible to meropenem, minocycline and amoxicillin/ clavulanic and resistant to levofloxacin, piperacillin and TMP-SMX. 8 Treatment consisted of ceftriaxone (2 weeks) and meropenem (17 days) respectively with clinical improvement in both cases. 8 Abbas et al (2018) reported a case of neonatal sepsis with a multidrug resistant strain of R. ornithinolytica isolated in blood cultures of a 12 hrs-old infant.…”
Section: Bloodstream and Other Infectionsmentioning
confidence: 95%
“…42 Yamakawa et al (2016) described 2 cases of R. ornithinolytica infection in pediatric patients in whom R. ornithinolytica was detected in blood culture samples. 8 Patients were 3 and 7-year-old and had IgAnephropathy and myeloid leukemia respectively. 8 In the first case, antibiotic susceptibility testing reported susceptibility to ceftriaxone, amoxicillin/clavulanic acid and TMP-SMX, and resistance to ciprofloxacin, minocycline and fosfomycin.…”
Section: Bloodstream and Other Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Septic arthritis and sepsis in general [6,7] is possibly a major clinical consequence of this bacterial infection [8,9]. Children, especially in immunocompromised conditions are vulnerable in manifesting clinically significant complicated infections [10].…”
Section: Discussionmentioning
confidence: 99%